2021
DOI: 10.1158/1078-0432.ccr-21-1165
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Molecular Analysis of Inflammatory Myofibroblastic Tumors Reveals Diverse Genomic Landscape and Potential Predictive Markers for Response to Crizotinib

Abstract: Purpose: The European Organization for Research and Treatment of Cancer (EORTC) clinical phase II trial 90101 “CREATE” showed high antitumor activity of crizotinib, an inhibitor of anaplastic lymphoma kinase (ALK)/ROS1, in patients with advanced inflammatory myofibroblastic tumor (IMFT). However, recent findings suggested that other molecular targets in addition to ALK/ROS1 might also contribute to the sensitivity of this kinase inhibitor. We therefore performed an in-depth molecular characte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…In ULs, chromothripsis occurs rarely, while more subtle chromosomal alterations are relatively common, especially in MED12 wild-type lesions 4. In IMT, complex chromosomal rearrangements including chromothripsis have been detected in a few metastatic tumors 43,44. In our analysis, 1 tumor (My6290m3) with strong ALK IHC positivity showed clear chromothripsis of the ALK harboring chromosome 2.…”
Section: Discussionmentioning
confidence: 54%
“…In ULs, chromothripsis occurs rarely, while more subtle chromosomal alterations are relatively common, especially in MED12 wild-type lesions 4. In IMT, complex chromosomal rearrangements including chromothripsis have been detected in a few metastatic tumors 43,44. In our analysis, 1 tumor (My6290m3) with strong ALK IHC positivity showed clear chromothripsis of the ALK harboring chromosome 2.…”
Section: Discussionmentioning
confidence: 54%
“…In the absence of large randomized studies, we must rely on published clinical cases, as well as choose treatments by analogy with the responses obtained in other cancers with the same genetic mutations. In-depth molecular characterization of archival IMT tissue from 24 patients enrolled in the CREATE trial revealed extensive molecular heterogeneity including DNA damage repair mechanisms (19/24), Wnt signaling (16/24), and cell-cycle and cell death pathway (13/24) [ 42 , 48 ]. Although the authors identified 17 potentially actionable recurrent gene aberrations including ATRX , FAT1 , FCRL4 , FOXO1 , NUTM2B , PIK3CA , SMAD4 , and TP53 , no ROS1 -rearranged tumor has been identified.…”
Section: Current Treatmentsmentioning
confidence: 99%
“…Although the authors identified 17 potentially actionable recurrent gene aberrations including ATRX , FAT1 , FCRL4 , FOXO1 , NUTM2B , PIK3CA , SMAD4 , and TP53 , no ROS1 -rearranged tumor has been identified. In the CREATE trial, the patient who had the objective response in the ALK-negative cohort had an ETV6-NTRK3 fusion which may have made the IMT sensitive to crizotinib [ 48 ].…”
Section: Current Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observation of recurrent translocations at 2p23 with identification of the anaplastic lymphoma kinase ( ALK ) gene in fusion proteins led to the recognition that IMT cases with these alterations have intermediate malignant potential 6–8 . Translocations involving ALK may be present in 50%–60% of IMT cases, although there is heterogeneity 1,4,9 . In cases with absent ALK protein expression or translocation, additional target genes, such as ROS1, NTRK, RET , and PDGFR‐beta , have been identified 9 …”
Section: Introductionmentioning
confidence: 99%